PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI FOGGING DI RT 01/RW 02 BENGKONG SADAI - Sari , Eva Velisa; Saputra, Dedy; Oktaviana , Tanya; Hasibuan , Imam Abdullah; Septiandi , Egy; Jarti , Nanda; Sanusi , Sanusi; Basar , Abdul Rohmad (PUAN INDONESIA, 2025)
Kuliah Pengabdian Masyarakat (KPM) activity at Ibnu Sina University was conducted to evaluate the level of involvement of residents in RT 01/RW 02, Bengkong Sadai Village, in the fogging outreach program organized by the health department. Through a participatory qualitative method, the KPM team conducted direct observations in the field and held focus group discussions (FGD) with residents and health cadres. The findings showed that although the majority of residents understood the importance of fogging, their level of involvement in the activity was still low, due to a lack of technical understanding and minimal follow- up after the outreach was conducted. As a form of contribution, the KPM team offered solutions through training for health cadres and the development of simple educational media to increase community understanding. This initiative proved to be able to arouse residents' enthusiasm in supporting the implementation of the fogging program. This activity also serves as a real example of synergy between academic circles, village government, and the community. To maintain the sustainability of the program, the team recommends regular accompaniment and a system for monitoring citizen participation on an ongoing basis.